Pengaruh partisipasi penyusunan anggaran dan asimetri informasi terhadap senjangan anggaran pada badan daerah Kabupaten Bojonegoro - Taufiqurrahman, Mohammad Aviciena; Widajantie, Tituk Diah (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to examine and prove the effect of budgetary participation and information asymmetry on budgetary slack in the Bojonegoro district agency. Budgetary slack requires monitoring because it can have a bad impact on the organization if it is not done wisely. The study used quantitative methods with primary data sources or questionnaires distributed directly to respondents. The research sample was taken by random sampling technique and the determination of the sample using the slovin formula. The data analysis technique in this research is using the SmartPLS windows v.3.0 application software. the results of the study prove that the variable of budgetary participation has no effect on budgetary slack. Furthermore, the information asymmetry variable has an effect on budgetary slack.